STUDENT’S PERCEPTION ON BULLYING AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Shani Indri Astuti (PBI 15 UMY 041, 2015)
*41 The researcher raised the topic of bullying because bullying became a major topic that is always discussed. The cases of bullying that usually publish on television or newspapers are just cases of violence, while bullying may not be just about violence. The researcher conducted this study at English Education Departmen of Universitas Muhammadiyah Yogyakarta. In conducting this study, the researcher used qualitative methods to determine the types of bullying that often occured in English Education Department of Universitas Muhammadiyah Yogyakarta and student’s opinion about bullying. The researcher chose batch 2012, 2013, and 2014 from English Education students, conducted observations and interviews to obtain the data. Observation were made for three times in different batches. Meanwhile, the researcher conducted the interviews with four students with those batches. The respondents that chose by the researcher was the respondent who commited acts of bullying or who are became victims of bullying. The findings showed that most of students in English Education Department of Universitas Muhammadiyah Yogyakarta did bullying action against their friends. Types of bullying that commonly happened in PBI UMY are Verbal Bullying, Cyber Bullying and Physical Bullying. The victim of bullying felt common because bullying was often done in class. Bullying that happened in class was very distrubtive. The class is not conducive and bullying disturbed concentration in the class.